Beyond Appeasement Interpreting Interwar Peace Movements in World Politics - Lynch, Cecelia (Book collections on Project MUSE., 1999)
The interwar peace movements were, according to conventional interpretations, naive and ineffective. More seriously, the standard histories have also held that they severely weakened national efforts to resist Nazi Germany and Stalinist Russia. Cecelia Lynch provides a long-overdue reevaluation of these movements. Throughout the work she challenges these interpretations, particularly regarding the postwar understanding of Realism, which forms the basis of core assumptions in international relations theory.The Realist account labels support for interwar peace movements as idealist. It holds that this support-largely pacifist in Britain, largely isolationist in the United States-led to overreliance on the League of Nations, appeasement, and eventually the onset of global war. Through a careful examination of both the social history of the peace movements and the diplomatic history of the interwar era, Lynch uncovers the serious contradictions as well as the systematic limitations of Realist understanding and outlines the making of the structure of the world community that would emerge from the war.Lynch focuses on the construction of the United Nations as evidence that the conventional history is incomplete as well as misleading. She brings to light the role of social movements in the formation of the normative underpinnings of the U.N., thus requiring scholars to rethink their understanding of the repercussions of the interwar experience as well as the significance of social movements for international life.